An Exploration of Productivity Costs and Years of Potential Life Lost: Understanding the Impact of Premature Mortality From Injury in Mongolia - Purevgerel Altangerel; Otgonbayar Damdinbazar; Urjinbadam Borgilchuluun; Dorjmyagmar Batbayar; Batmanduul Erdenebat; Tseden Purevdorj; Gantugs Yundendorj (SAGE Publishing, 2023)
This study estimates the years of potential life lost (YPLL), years of potential productive life lost (YPPLL), and cost of productivity loss (CPL) owing to injury-related mortalities in Mongolia. By implementing a retrospective cohort study, the study used secondary mortality data for Mongolia from 2016 to 2020 from the Health Development Center. Our study incorporates information on 13 551 fatalities from injuries and external factors, with the aim of estimating YPLL, YPPLL, and CPL associated with the leading causes injury-induced deaths. These include exposure to toxic substances, road accidents, homicides, suicides, and falls. Our findings reveal majority of the losses occur because of exposure to poisonous chemicals, road accidents, suicides, falls, and homicides. Furthermore, 444 550 years of potential life are lost owing to injury-related mortalities, in which YPPLL accounts for 338 482 years. The CPL caused by these premature deaths during the study period accounts for $1.368 billion. Notably, YPLL, YPPLL, and CPL rates are significantly higher in males than in females. The YPLL from exposure to poisonous chemicals is higher than those caused by other factors. This study is the first to calculate the CPL owing to YPLL from injury in Mongolia.